2016
DOI: 10.11114/ijsss.v4i2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Customary Land Tenure Security in Western Province of Zambia

Abstract: This paper presents the empirical findings of a research study undertaken in the Western Province of Zambia. The principal objective was to explore if the issuance of land ownership certificates (LOCs) improves the customary landholders" perceptions of security of tenure. Thus, we test a null hypothesis that: "There are no significant differences in the perceived security of tenure between customary landholders with land ownership certificates and customary landholders without land ownership certificates". A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Their findings revealed that no statistical association was observed to impact food security from government land. For Zambia, less research was carried out to explore the land tenure systems [35]. The study by Smith [36] in Zambia demonstrated that formal land titles enhanced investment and were more profitable, with higher output on agricultural productivity.…”
Section: Conceptual Link On Determinants Of Food Securitymentioning
confidence: 99%
“…Their findings revealed that no statistical association was observed to impact food security from government land. For Zambia, less research was carried out to explore the land tenure systems [35]. The study by Smith [36] in Zambia demonstrated that formal land titles enhanced investment and were more profitable, with higher output on agricultural productivity.…”
Section: Conceptual Link On Determinants Of Food Securitymentioning
confidence: 99%
“…Although there is more evidence that reflects the efforts of the Governmental organization and development sector organizations in the provision of water supply and sanitation services but less evidence on sustainability is available (Montgomery & Bartram, 2010). WASH as a concept in education is a strategic intervention towards providing schools with safe drinking water, improved hygiene, and sanitation facilities (Jain et al, 2019). The above-mentioned definition shows that the nature of WASH sustainability is a multicriteria and requires an integrated framework for its measurement and different factors and sub-factors must be known to assess the sustainability of WASH-related systems.…”
Section: Sustainable Wash Servicesmentioning
confidence: 99%
“…In fact, security of land tenure is more of a psychological variable that consists of both the states of thinking and feeling [ 20 , 28 , 29 , 30 ]. Thus, despite the legal projection of land tenure security, it is a matter of the state of mind of the landholder.…”
Section: Land Tenure Security As Preventive Medicine: a Conceptual Ap...mentioning
confidence: 99%
“…Most indicators of land tenure security are developed by international organizations or NGOs involved in the land sector where land tenure security is usually translated into few indicators and packaged into evaluation tools or frameworks [ 24 ]. Mention can be made of, including but not limited to, the USAID Land Tenure and Property Right Assessment Tools—a collection of instruments designed around the Land Tenure and Property Rights Matrix that can be used by USAID missions to expand upon land tenure and property rights themes in their respective countries and determine how these contribute to or impede development programming [ 72 ]; Property Rights Index (Prindex)—a global survey that collects data on rates of property documentation and perceptions of tenure security [ 73 ]; Global Land Indicators Initiative—a collaborative and inclusive process for developing Global Land Indicators [ 22 ]; World Bank Land Governance Assessment Framework—a diagnostic instrument to assess the state of land governance at the national or sub-national level [ 74 ]; and LANDex—a global land index that puts people at the center of land data, democratizing land monitoring, and building a data ecosystem where all voices can be heard [ 75 ] and a host of land tenure security indicators by individual researchers and scholars [ 20 , 21 , 24 , 76 ].…”
Section: Synopsis and Gaps In Land Tenure Security And Health Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation